2003
DOI: 10.1073/pnas.0438043100
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that affect the ability of the vnd/NK-2 homeoprotein to regulate gene expression: Transgenic alterations and tertiary structure

Abstract: The importance in downstream target regulation of tertiary structure and DNA binding specificity of the protein encoded by the vnd͞NK-2 homeobox gene is analyzed. The ectopic expression patterns of WT and four mutant vnd͞NK-2 genes are analyzed together with expression of two downstream target genes, ind and msh, which are down-regulated by vnd͞NK-2. Three mutants are deletions of conserved regions (i.e., tinman motif, acidic motif, and NK-2 box), and the fourth, Y54M vnd͞NK-2, corresponds to a single amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
(65 reference statements)
3
27
0
Order By: Relevance
“…For instance, Pax5 and Bap interact with Gro/TLE through sequences besides their octapeptide/eh1 domains, and AML1 lacking its WRPY motif retains some Gro-binding activity (11,21,40). Importantly, the occurrence of multiple Gro-binding sites within repressors might explain why mutations in some eh1 domains lead to surprisingly mild phenotypes (12,16,39). It is conceivable that synergistic interactions between multiple weak binding domains within repressors and in Gro/TLE provide composite interfaces that allow for high-affinity protein interactions and hence for robust repressor capability in vivo.…”
Section: Recruitment Of Gro By Repressors Containing Eh1-like Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Pax5 and Bap interact with Gro/TLE through sequences besides their octapeptide/eh1 domains, and AML1 lacking its WRPY motif retains some Gro-binding activity (11,21,40). Importantly, the occurrence of multiple Gro-binding sites within repressors might explain why mutations in some eh1 domains lead to surprisingly mild phenotypes (12,16,39). It is conceivable that synergistic interactions between multiple weak binding domains within repressors and in Gro/TLE provide composite interfaces that allow for high-affinity protein interactions and hence for robust repressor capability in vivo.…”
Section: Recruitment Of Gro By Repressors Containing Eh1-like Motifsmentioning
confidence: 99%
“…In this report, we have shown that eh1 motifs are prevalent among members of various transcription factor families and have further demonstrated that one of these, specifically, the ZnF protein Odd, requires its eh1 Gro-binding domain for blocking gene expression in vivo. While our work was in progress, three additional eh1-containing proteins, shown in this paper to complex with Gro in vitro, were found to behave as repressors in vivo, i.e., Slp (1, 2), BarH1 (41), and Vnd (16,39). These reports independently support our conclusions and, along with the results presented here, suggest that a significant number of uncharacterized transcriptional regulators, containing eh1-related motifs, function as Gro-dependent repressors.…”
Section: Recruitment Of Gro By Repressors Containing Eh1-like Motifsmentioning
confidence: 99%
“…In principle, ind can be activated in both regions by the combination of low levels of the Dorsal gradient and EGF signaling, but expression is kept off in the ventral neurogenic ectoderm by Vnd, a sequencespecific transcriptional repressor that is activated by intermediate levels of Dorsal ( Fig. 1) (23)(24)(25). As a result of this repression, ind expression is restricted to lateral regions of the neurogenic ectoderm.…”
Section: Cell-cell Interactions Produce Additional Dorsal Gradient Rementioning
confidence: 99%
“…Previously, it has been reported that the amino acid residues at the positions 3 and 5 (Vnd 547 and 549, respectively) of the N-terminal arm as well as residues at the positions 47, 50, and 54 (Vnd 591, 595, and 598, respectively) of the recognition helix in HD directly contact with the bases of the DNA (5,9,16). In addition to the residues directly involved in base-specific interactions, amino acid side chains at the positions that do not contact any DNA bases are believed to affect the interaction of the HD with its target DNA, and thus may be important functionally.…”
Section: Kinetic Analysis Of Alanine Substitutions Within Either Homementioning
confidence: 99%